Features of Legal Regulation of Employment Contracts with Seasonal and Temporary Employees - A. Ya. Radzividlo (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on studying peculiarities of employment contracts with seasonal and temporary employees in Ukraine. The employment contract as the basis of the origin of labor relations with seasonal and temporary employees has been researched. The norms of the decrees of the Presidium of the Supreme Rada of the USSR “On working conditions of temporary employees and officials” dated from September 24, 1974 No. 311-09 and “On working conditions of employees and officials engaged in seasonal work” dated from September 24, 1974 No. 310-09 have been analyzed .